2002
DOI: 10.1080/13548500220139368
|View full text |Cite
|
Sign up to set email alerts
|

Predicting protected sexual behaviour using the Information-Motivation-Behaviour skills model among adolescent substance abusers in court-ordered treatment

Abstract: The Information-Motivation-Behavioural skills model (Fisher & Fisher, 1992) was used to predict condom use among adolescents residing in a court-ordered inpatient substance abuse treatment programme (N = 271; 181 male and 90 female, primarily of minority ethnicity). In a predictive structural equation model, demographic variables, HIV transmission knowledge, and motivational variables of pro-condom norms and attitudes, and perceived susceptibility predicted condom use skills and condom use self-efficacy. Along… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
41
0
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(50 citation statements)
references
References 32 publications
(38 reference statements)
6
41
0
3
Order By: Relevance
“…Various studies have shown that knowledge is an insufficient determinant to change risk behavior (Fishbein, Middlestadt, & Hitchcock, 1994). While providing adequate information is of public health value, information or knowledge of condom use appears insufficient in predicting condom use (Cornman, Schmiege, Bryan, Benziger, & Fisher, 2007;Kalichman et al, 2002). However, as in the original model, the important role of self-efficacy as a substantial component of behavioral skills was confirmed.…”
Section: Discussionmentioning
confidence: 59%
“…Various studies have shown that knowledge is an insufficient determinant to change risk behavior (Fishbein, Middlestadt, & Hitchcock, 1994). While providing adequate information is of public health value, information or knowledge of condom use appears insufficient in predicting condom use (Cornman, Schmiege, Bryan, Benziger, & Fisher, 2007;Kalichman et al, 2002). However, as in the original model, the important role of self-efficacy as a substantial component of behavioral skills was confirmed.…”
Section: Discussionmentioning
confidence: 59%
“…Some researchers have been critical of this approach. Jemmott, Jemmott, Fong and McCaffree (1999) indicated that self-reporting measures used on risky sexual behaviour (which is a private behaviour) are, to some degree, unintentionally or intentionally inaccurate while Kalichman, Stein, Malow, Averhart, Devieux, Jennings, et al (2002) indicate that self-reporting may lead to concealment of behaviours and therefore under-reporting. More recently, McAuliffe, Difranceisco and Reed (2007) argued that, in self-reporting, respondents tend to give socially desirable answers.…”
Section: Discussionmentioning
confidence: 99%
“…Risky sexual behavior has been alternatively defined by specific indicators (e.g., number of partners, condom use, sexual debut) (Blum et al, 2000;Smith, 1997), composite scores (Boyer et al, 2000;Donenberg et al, 2001), or both (Doljanac & Zimmerman, 1998;Pinkerton et al, 1998). We assessed adolescent self-reported global risky sexual behavior, a composite score consisting of four high-risk behaviors that have been linked to HIV risk in previous research: multiple partners (Fisher et al, 1999;Kalichman et al, 2002), sex while using drugs and alcohol , sex with someone whose history is not well known and therefore could be a high-risk partner (Eiser & Ford, 1995;Metzler, Noell, Biglan, Ary, & Smolkowski, 1994;Rickman, Lodico, DiClemente, & Morris, 1994), and sex without a condom (Fisher et al, 1999;Kalichman et al, 2002).…”
Section: The Information-motivation-behavioral Skills (Imb) Modelmentioning
confidence: 99%